Evolutionary reversion of editing sites of ndh genes suggests their origin in the Permian-Triassic, before the increase of atmospheric CO2 - Martin, Mercedes; Marín, Dolores; Serrot, Patricia H.; Sabater, Bartolome (Frontiers in Ecology and Evolution, 2015)
The plastid ndh genes have hovered frequently on the edge of dispensability. They are absent in the plastid DNA of many algae and certain higher plants and present editing sites requiring C-to-U corrections of primary transcripts. The evolutionary origin of editing sites and their loss due to C-to-T reversions at the DNA level are unknown and must be related to the dispensability of the ndh genes in specific environments. In order to better understand the evolution of ndh gene editing sites, we have created expandable data banks with the 12 editing sites of the ndhB gene (600 GenBank sequences) and both editing sites of the ndhF gene (1,600 GenBank sequences). Since their origin via T-to-C mutations that probably occurred between 300 and 200 Myr BP (Permian-Triassic), ndh editing sites have undergone independent and random C-to-T reversions in the different angiosperm lineages. Some of these reversions appear early in angiosperm diversification. Old C-to-T reversions can be traced back to radiation steps that gave origin to main classes, orders and some families.